Desiminasi Perdasus Nomor 25 Tahun 2013 Tentang Pembagian, Penerimaan Dan Pengelolaan Keuangan Dana Otonomi Khusus Bagi MRP Dan DPR Provinsi Papua - Agustinus Salle (The Community Engagement Journal, 2018)
This study describes about the community engagement activity in regard to conduct the dissemination of special regional regulations number 25 in 2013 on the distribution, acceptance and management of the financial special autonomy fund for members of MRP and DPRP/DPRD in Papua Province. This activity has purpose to provide an understanding for the representatives of MRP and DPRP/DPRD in monitoring and managing special autonomy fund. The participants of this activity are 90 people. Then, the result of this activity is expected to enhance an understanding of MRP and DPRP/DPRD representatives in regard to monitoring how special autonomy fund can be managed in Papua Province